Kontribusi Mahasiswa MBKM: Meningkatkan Pemahaman Matematika Santri di Pondok An-Nahdloh, Selangor - Hasanah, Siti Maulidah; Shodiq, Ahmad Ja’far; Bali, Muhammad Mushfi El Iq (Redtech Putra Benua, 2024)
An-Nahdloh Islamic Boarding School is a tahfidz boarding school located in Tanjong Sepat, Banting, Selangor, offering three main programs: the tahfidz program, the diniyah program, and the An-Nahdloh SB-SMP program. As part of an international MBKM (Merdeka Belajar Kampus Merdeka) activity, several students from Universitas Nurul Jadid carried out community service activities aimed at exploring the potential of the students, which had not been fully realized. One of the efforts to uncover this potential was organizing a Math Day, designed to assess students' understanding of mathematics through educational games within the boarding school environment. It was concluded that the community service activities, conducted over a period of five months, were successful.